Development of ITO layers for high efficiency CdTe solar cells - Khrypunov, G.S. (Functional Materials, 2004)
The high-frequency non-reactive magnetron sputtering regimes have been found providing ITO films exhibiting a necessary combination of optical and electrical paramet ers of those layers in ITO/CdS/CdTe solar cells. Идентифицированы режимы высокочастотного нереактивного магнетронного распыления пленок ITO, которые обеспечивают необходимое сочетание оптических и электрических параметров этих слоев в составе солнечных элементов ITO/CdS/CdTe. Ідентифнковано режими високочастотного нереактивного магнетронного розпилення шарiв ITO, які забезпечують необхідне поєднання оптичних i електричних параметрiв цих шарів у складі високоефективних сонячних елементів ITO/CdS/CdTe.